Fintech development in the People's Republic of China and its macroeconomic implications - Yiping Huang (Asian Development Bank Institute (ADBI), 2020)
FinTech has been transforming the financial landscape in the People's Republic of China. Its leading FinTech businesses such as mobile payment services and big data-based online lending are at the frontier of global development. At the same time, it also creates new problems, illustrated by the rise and fall of the peer-to-peer lending industry. The soon-to-be implemented central bank digital currency/electronic payment (DC/EP) may also bring about fundamental changes to the financial system. Overall, the FinTech development not only makes financial inclusion an achievable goal but also has important implications for financial and macroeconomic stability.
Keywords: G23; O31; E60; 330; FinTech; financial inclusion; financial risks; macroeconomic stability